Food security and the urban informal economy in South Africa: The state of knowledge and perspectives from street-food traders in Khayelitsha - Even-Zahav, Etai (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.